Potential Roles of the Gut Microbiota in Pancreatic Carcinogenesis and Therapeutics - Yang, Qiaoyu; Zhang, Jihang; Zhu, Yin (Frontiers in Cellular and Infection Microbiology, 2022)
The intestinal microenvironment is composed of normal gut microbiota and the environment in which it lives. The largest microecosystem in the human body is the gut microbiota, which is closely related to various diseases of the human body. Pancreatic cancer (PC) is a common malignancy of the digestive system worldwide, and it has a 5-year survival rate of only 5%. Early diagnosis of pancreatic cancer is difficult, so most patients have missed their best opportunity for surgery at the time of diagnosis. However, the etiology is not entirely clear, but there are certain associations between PC and diet, lifestyle, obesity, diabetes and chronic pancreatitis. Many studies have shown that the translocation of the gut microbiota, microbiota dysbiosis, imbalance of the oral microbiota, the interference of normal metabolism function and toxic metabolite products are closely associated with the incidence of PC and influence its prognosis. Therefore, understanding the correlation between the gut microbiota and PC could aid the diagnosis and treatment of PC. Here, we review the correlation between the gut microbiota and PC and the research progresses for the gut microbiota in the diagnosis and treatment of PC.